Early tolerance mechanisms in citrus: transcriptome and hormone profiling of NPR1-mediated responses to Candidatus Liberibacter asiaticus - Sarkar, Poulami; Wang, Chunxia; Levy, Amit (Frontiers in Plant Science, 2026)
Huanglongbing (HLB), caused by Candidatus Liberibacter asiaticus (CLas), is the most destructive citrus disease worldwide, severely reducing yield and fruit quality. Although no naturally resistant cultivars are available, citrus plants overexpressing Arabidopsis NPR1 (AtNPR1) display enhanced tolerance, yet the molecular mechanisms underlying this phenotype remain insufficiently understood. To uncover early transcriptional events associated with tolerance, we performed comparative RNA-seq and phytohormone profiling of susceptible wild-type (WT) and tolerant AtNPR1-overexpressing (AtNPR1-OE) Duncan grapefruit at 0, 6, and 24 hours post infection (hpi). Before infection, AtNPR1 plants downregulated genes involved in cytoskeleton organization, cell wall biogenesis, and receptor signaling, suggesting a primed basal defense state. After CLas exposure, AtNPR1 plants exhibited stronger and earlier transcriptional reprogramming, with substantially more differentially expressed genes at 6 hpi than WT. At 24 hpi, AtNPR1 plants showed suppression of callose synthase genes and selective induction of β-1,3-glucanases, indicating more controlled phloem callose regulation. Concurrently, attenuated expression of respiratory burst oxidase homologs and ROS-associated genes suggested a moderated and less damaging oxidative burst. AtNPR1 plants maintained stable levels of salicylic acid, and gibberellins while preventing the CLas-induced induction of abscisic acid observed in WT. Collectively, these findings reveal that AtNPR1 overexpression enhances HLB tolerance by integrating early transcriptional reprogramming with balanced structural, oxidative, and hormonal responses. This study provides a mechanistic framework for understanding NPR1-mediated tolerance to CLas during the initial stages of infection.